Management of banking and financial services - Suresh, Padmalatha (Pearson, 2010)
Management of Banking and Financial Services focuses on the basic concepts of banking and financial services, and how these concepts are applied in the global banking environment as well as in India. In addition to presenting the big picture of the banking and financial services industry, the book also provides useful tips on the trade-off between risk and return. The book examines all of the key aspects of the banking and financial services industry, highlighting both global and Indian applications; it includes three new chapters to address contemporary issues, and provides revised and updated material in all the other chapters; explains concepts through case studies on organisations such as Barclays Bank, Corporation Bank, South Indian Bank, and the State Bank of India. It also includes pedagogical features such as chapter objectives, chapter-end summaries, chapter-end questions, solved problems, illustrations, additional topics for further research, and boxes that present examples and cases.